First report of virus detection in Ficus carica in Austria - Eduviges Glenda BORROTO FERNANDEZ; Toufic ELBEAINO; Florian FÜRNSINN; Anna KEUTGEN; Norbert KEUTGEN; Margit LAIMER (Phytopathologia Mediterranea)
Ficus carica is one of the most ancient cultivated crops, and is grown mainly in the Mediterranean region. In Austria, due to milder winters and longer warm periods than normal, figs are becoming more productive and popular among private growers. For future propagation of some fig varieties, the phytosanitary status of eight fig accessions, representing four Austrian genotypes maintained in a varietal collection plot, was investigated using PCR assays for presence of eight fig-infecting viruses. The four fig trees were infected with fig mosaic virus (FMV), fig badnavirus 1 (FBV-1), fig leaf mottle-associated virus 1 (FLMaV-1), fig mild mottle-associated virus (FMMaV) and fig fleck-associated virus (FFkaV); whereas fig leaf mottle-associated virus 2 (FLMaV-2), fig latent virus 1 (FLV-1) and fig cryptic virus 1 (FCV-1) were not detected. The sequences of PCR amplicons obtained from different viruses and samples showed greatest nucleotide variability of 0.5% for FBV-1, 12% for FLMaV-1, 16.3% for FMV, 14% for FMMaV, and 15% for FFkaV, when compared to their homologues in GenBank. A phylogenetic tree for FMV constructed based on partial RNA1 sequences showed that the Austrian isolates were most closely related to previously described Spanish and Greek isolates. The different symptoms observed in the tested trees were mainly in similar to with those reported for FMV, the agent of fig mosaic disease. This is the first report on the presence of fig mosaic-associated viruses in Austria.